Morphology 2024 Conference Programme and Book of Abstracts (Masaryk University Press, 2024)
The conference book of Morphology 2024 compiles abstracts of the latest research results presented at the 55th International Congress of Czech Anatomical Society, and the 60th Lojda Symposium on Histochemistry, held in Telč in 2024. This conference brings together leading experts and researchers in neurosciences, molecular and cell biology, developmental morphology, clinical anatomy, histology, anthropology, and anatomical education. The conference book offers valuable insights for scientists and educators interested in the future trends in morphological sciences.